1995
DOI: 10.1037/0022-006x.63.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Supervision: Its contributions to treatment efficacy.

Abstract: The efficacy of supervision in training of psychotherapists is discussed in relation to (a) trainees' attitudes, beliefs, and skills, (b) trainee's performance in the therapist role, (c) interactional process events in supervision and psychotherapy, and, (d) client change. Although investigations to date suggest the potential of supervision for teaching advanced skills of psychotherapy, few studies exist that examine directly the relation of therapist performance and client change to supervision. There are vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
167
1
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(179 citation statements)
references
References 44 publications
4
167
1
5
Order By: Relevance
“…the trainee's ability to show empathy have been well documented (Holloway & Neufeldt, 1995;Lambert & Arnold, 1987).…”
mentioning
confidence: 99%
“…the trainee's ability to show empathy have been well documented (Holloway & Neufeldt, 1995;Lambert & Arnold, 1987).…”
mentioning
confidence: 99%
“…Additionally, unsuccessful therapies are characterized by delayed interventions on resources activation and a weak therapeutic alliance (Gassmann and Grawe, 2006). While the quality of the early alliance has been proved to be a reliable predictor of therapeutic success (Horvath and Bedi, 2002;Orlinsky et al, 2004), the existing evidences has shown that it is difficult to influence the therapeutic alliance intentionally Holloway and Neufeldt, 1995).…”
Section: Therapeutic Change In Behavioural Disorder Treatmentmentioning
confidence: 99%
“…Worthen and McNeill (1996) analysed interview data from trainee counsellors concerning good supervision experiences using phenomenological analysis. However, Holloway and Neufeldt (1995) and Bernard and Goodyear (1998) warn against relying on satisfaction ratings, as they may or may not relate to client outcome.…”
Section: 4mentioning
confidence: 99%
“…It doesn't seek to bracket out complexities in order to determine causality or allow for generalisability (e.g. Milne, 2007;Holloway and Neufeldt, 1995).…”
Section: Implications For the Current Researchmentioning
confidence: 99%